Mechanical and thermal properties of Montmorillonite filled date palm leaf fiber reinforced recycled polyethylene terephthalate nanocomposites - Alireza Dehghani, 1984-; Mat Uzir Wahit, supervisor; Azman Hassan, supervisor; Fakulti Kejuruteraan Kimia (2012)
Thesis (Sarjana Sains (Teknologi Polimer)) - Universiti Teknologi Malaysia, 2012